If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3)(24x)(2x + -3) * 4 = 0 Remove parenthesis around (24x) 3 * 24x(2x + -3) * 4 = 0 Reorder the terms: 3 * 24x(-3 + 2x) * 4 = 0 Reorder the terms for easier multiplication: 3 * 24 * 4x(-3 + 2x) = 0 Multiply 3 * 24 72 * 4x(-3 + 2x) = 0 Multiply 72 * 4 288x(-3 + 2x) = 0 (-3 * 288x + 2x * 288x) = 0 (-864x + 576x2) = 0 Solving -864x + 576x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '288x'. 288x(-3 + 2x) = 0 Ignore the factor 288.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-3 + 2x)' equal to zero and attempt to solve: Simplifying -3 + 2x = 0 Solving -3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 0 + 3 2x = 0 + 3 Combine like terms: 0 + 3 = 3 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5Solution
x = {0, 1.5}
| 5+0.25=2+0.35 | | 3000-120s=4000-160s | | 5+x=2+x | | 8(4)(2x+5)= | | 15w=2.10 | | x^2=37.8175 | | 15w=210 | | 24+3(4-2)2*2(2x+5)= | | U^2+17u+49=0 | | -x^2-18=0 | | 21a^2+23ab+6b^2=0 | | 41+-8x=-6x-23 | | 2377960+26d=2067959+125d | | 4(3x-2)=2(10x-4) | | -2x-4.5+7x= | | 3000000=2377960+26d | | 2y-3=17 | | 3y+1=-7 | | 4y=-12+16 | | 0.95x+0*300=0.70(x+3000) | | 2x+x+6=24 | | (-8x)(3x^2)= | | m^2n^2-8mn+32= | | 3x^2*-8x= | | 8p^3+27=0 | | 54x^2-126xy-48y^2=0 | | 1996+43w=7385-67w | | 7385-67w=6250 | | 9x-4x(x-2)=x+20 | | 7385-67w=3200 | | 8(6k+3)=216 | | -75= |